Evaluation of outcome of bilateral cleft lip repair using a simplified scoring system (Bangladesh Medical Journal Khulna, 2025)
Background: Bilateral cleft lip is a complex congenital deformity of face. Restoration of the normal facial form is one of the primary goals for reconstructive surgeons. Surgical repair of bilateral cleft lip is complex and still controversial, though various techniques have been reported and described in detail. The repair can be a challenge even to an experienced surgeon and the results of primary repair of bilateral cleft lip traditionally have been less satisfactory than those of unilateral cleft lip. Objective: This study aimed to evaluate the surgical outcome of bilateral cleft lip surgery by the modified Millard technique using a simplified scoring system. Materials and Methods: This study was conducted from January 2013 to December 2021 at a private Hospital, a cleft center of Smile Train. 46 cases of bilateral cleft lip were operated by the modified Millard technique during this study period. Data analysis included age and sex of patients, type of cleft deformity and type of surgery (primary or secondary) and whether the cleft deformity was syndromic or non-syndromic. Technique of repair, surgical outcome and complications were also recorded. The photographic evaluation was done between 3 months to 3 years after lip operation by a surgeon and a social worker on three regions- lip, nose and general facial appearance with a total score of 10. Results: A total of 46 cases of BCL (Bilateral Cleft Lip) comprising of 29 males and 17 females were operated which constituted 9.2% (46/500) of all cases of cleft surgery done during this study period. The age of patients at the time of surgery ranged between 4 months and 16 years. 38 patients had bilateral cleft lip and palate deformities and 8 had only bilateral cleft lip deformities. Primary surgery was performed in 45(97.82%) cases and secondary (revision) surgery was performed in only 1(2.18%) case. There was no syndromic case. All cases were operated by the modified Millard technique. Aesthetic outcome was evaluated by a simplified scoring system. The outcome was good with this repair technique and evaluated by this scoring system. Conclusion: This is an effective scoring system to evaluate the outcome of bilateral cleft lip repair.Bang Med J Khulna 2022; 55 : 03-07